Emergence of COVID-19 Infection and Healthcare Workers in Karachi, Pakistan - Shabnam Naveed; Shobha Luxmi; Syed Masroor Ahmed; Zeeshan Ali; Syed Adnan Ali (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
Background: The Healthcare workers (HCWs) are at the forefront of care-giving and hence understanding of the knowledge, attitudes and practices among HCWs is necessary to identify potential risk factors of COVID-19 dissemination. Objective: The objective of the study was to investigate the knowledge, attitude and practice (KAP) regarding novel coronavirus disease 2019 (COVID-19) among healthcare workers in Karachi Pakistan. Material and Methods: This was a cross-sectional study using a self-reported questionnaire which enrolled all the HCWs (doctors, nurses, pharmacists and technicians) in hospitals of Karachi from March to May 2020.Binary logistic regression analysis was performed to estimate the odds ratio with 95% confidence interval for KAP of HCWs regarding COVID-19. P-values less than 0.05 were considered statistically significant. Results: The total of 547 participants included in study. HCWs gross category and clinical setting were found to be statistically associated with overall KAP (P<0.001 and P=0.048, respectively). Upon logistic regression analysis, KAP scores statistically differed across genders (? coefficient=2.115, SE =0.179 and P<0.001), age groups (? coefficient=2.098, SE =0.138 and P<0.001) and HCWs gross category (? coefficient=2.053, SE =0.135 and P<0.001). The nurses and technicians were found less likely for good KAP with reference to COVID-19 as compared to doctors and pharmacists. These results were found to be statistically significant with P-value less than 0.05; the odds for nurses and technicians were 0.35 and 0.10, respectively. Conclusion: The study demonstrated that HCWs had good knowledge, optimistic attitude and decent practice towards recent COVID-19 pandemic. However, their source of information regarding COVID-19 is not reliable and can adversely influence the KAP. Keywords: KAP; COVID-19; Outbreak; Pandemic; Healthcare Workers